Development of Pdn/g-C3N4 adsorbent for Hg0 removal – DFT study of influences of the support and Pd cluster size. (15th October 2019) - Liu, Shuai; Chen, Lin; Mu, Xueliang; Xu, Mengxia; Yu, Jiahui; Yang, Gang; Luo, Xiang; Zhao, Haitao; Wu, Tao
Graphical abstract: Highlights: The g-C3 N4 acts as a good support for single Pd atoms and Pd clusters. Pdn cluster size shows significant influence on the adsorption of mercury atoms. The g-C3 N4 has no influence on the adsorption of mercury on single Pd atoms. The g-C3 N4 activates seven sites on one Pd4 cluster for the adsorption of Hg atoms. Pd4 /g-C3 N4 is of potential to be used in mercury adsorption from coal-fired flue gas. Abstract: Elemental mercury in the flue gas is highly hazardous to the ecosystem. However, its removal from gas phase is of challenges as it is highly volatile, chemically very stable and insoluble in water. It is therefore imperative to develop novel adsorbents that are efficient in the removal of elemental mercury from gas mixtures. In this study, density functional theory (DFT) was adopted to assist the development of novel adsorbents for mercury removal based on the in-depth understanding of the adsorption of Hg 0 on g-C3 N4, single Pd atoms and Pdn(n=2–4) clusters as well as the influences of the support and the size of Pd clusters on Hg 0 adsorption. It is found that Hg 0 atoms are physically adsorbed on the pristine g-C3 N4 and are chemisorbed on the pure Pdn clusters and the Pdn /g-C3 N4 . The strongest adsorption happens on the Pd2 cluster and the Pd3 /g-C3 N4, while single Pd atoms doped on the g-C3 N4 do not adsorb Hg 0 atoms effectively. For a Pd4 cluster, there are at least four adsorption sites for the adsorption of Hg 0, while these sites become more active in the presence of the support and the number of active sites for Hg 0 adsorption on a Pd4 cluster doped on the g-C3 N4 becomes seven due to the enhanced charge transfer from Hg atoms to the Pd cluster and the g-C3 N4 surface. The most charge transfers are found to take place in the case of Pd2, Pd2 /g-C3 N4 and Pd3 /g-C3 N4, indicating the most intensive interactions between Hg 0 and these configurations. Moreover, the shortened Pd-Hg bonds in the Pd3 /g-C3 N4 and the Pd4 /g-C3 N4 also shows the enhanced mercury adsorption, while opposite phenomena were observed in the other two structures, i.e., the Pd/g-C3 N4 and the Pd2 /g-C3 N4 .